A DINOFLAGELLATE TBP‐LIKE FACTOR ACTIVATES TRANSCRIPTION FROM A TTTT‐BOX IN YEAST. Issue 2 (28th February 2022) - Zaheri, Bahareh; Veilleux‐Trinh, Charlotte; Morse, David
Abstract : Dinoflagellates do not have a typical TATA‐binding protein (TBP), a subunit of the general transcription factor TFIID complex. Instead, they have a TBP‐like factor (TLF) that has been shown to bind TTTT instead of TATA in vitro. The ability of TLF to act as a functional replacement of TBP in vivo has never been assessed, however. Here, we show that a dinoflagellate TLF can drive expression of a reporter gene controlled by a budding yeast promoter whose TATA box was mutated to TTTT. TLF is thus able to bind and activate the yeast RNA polymerase and appear to function normally in the TFIID complex.